IMPLEMENTASI KEBIJAKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 TERHADAP KINERJA BADAN LEGISLASI DPRD KABUPATEN MOROWALI - Hamzah, Hamzah (Katalogis, 2013)
This study aims to analyze the process of policy implementation of Law Number 32 Year 2004 on the performance of Legislation Morowali Regency, informants in the study consisted of the Chairman of Parliament Chairman of Faction Chairperson of the Commission, Member, SKPD. While the data analysis technique used is to reduce the data, presenting data, and describe and conclude and verify the data. The results showed the policy implementation process of the Act No. 32 of 2004 on the performance of Legislation Morowali district legislature has not so it can be a maximum of three indicators to measure in this study such as: first, communication was limited to communication which is run at the level of members of the Board legislation alone without involving stakeholders in the district Morowali. Second, the resources owned by a local parliament member Morowali inadequate. Third, the disposition is a member of Legislation lack of awareness of the responsibilities that have been run in to mandate him. While the factors that affect members of the legislature in carrying out the task is First Area. The total area owned by the District Morowali greatly affect the performance of a member of Legislation Morowali district legislature because most members of the legislative districts are located at a distance away from where they worked as a representative of the people. the lack of creativity and innovation in policy have so that the initiative comes from the Legislation is still so lacking. Should be as representative of the people expected to turn up the initiative of representatives of the legislative initiatives discussed based on the interests of their constituents without having to wait for the draft that is given by the executive.